Experience of a smartphone ambulatory ECG clinic for emergency department patients with palpitation: a single-centre cohort study. (16th August 2021) - Cullen, Julia; Reed, Matthew J.; Muir, Alexandra; Murphy, Ross; Pollard, Valery; Zangana, Goran; Krupej, Sean; Askham, Sylvia; Holdsworth, Patricia; Davies, Lauren
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and importance: Palpitation is one of the commonest presenting complaints to the emergency department (ED). Diagnosis depends on capturing an ECG during the episode. Unlike syncope, patients retain consciousness and therefore their ability to activate an ECG event recorder. The Investigation of Palpitation in the ED study demonstrated Food and Drug Administration approved AliveCor/Kardia device that links to a smartphone app was safe and effective. A Smartphone Palpitation and Pre-syncope Ambulatory Care Clinic was therefore established. Objective(s): To review the first year of patients attending the service to determine the number and cost-effectiveness of cardiac dysrhythmias diagnoses. Design: Single-center cohort study. Settings and participants: Royal Infirmary of Edinburgh, UK. All patients (over 16 years) presenting consecutively to ED with palpitation or pre-syncope, whose ECG was normal, had a compatible device and where an underlying cardiac dysrhythmia was possible were enrolled. Intervention: Ambulatory Care Clinic utilizing the AliveCor/Kardia device. Outcome measures and analysis: Number diagnosed with cardiac dysrhythmia and mean cost per diagnosis. Main results: Between 24 July 2019 and 23 July 2020, 290 consecutive patients were referred of age 16–80 years (mean 43.3, SD 15.0). One hundred twenty (41.4%) were male. Two hundred thirty-seven (81.7%) were fitted with the device and 220 (75.9%) underwent full investigation. Seventeen of 237 (7.2%) patients had a cardiac diagnosis (12 atrial fibrillation/flutter, 5 supraventricular tachycardia and 1 atrial tachycardia). Conclusions: There were 17 cardiac diagnoses (7.2%). The cost per symptomatic rhythm diagnosis was 358 GBP ( 415 Euro) and the cost per cardiac dysrhythmia diagnosis was 4570 GBP ( 5298 Euro). A smartphone-based event recorder clinic should be considered for ED palpitation patients.